Study of Complexation Patterns in the System Ni2+, MoO42–, P2O74–, Cit3–for the Development of Poly-Ligand Electrolytes (Study of complexation patterns) - T. Nenastina; M. Sakhnenko; S. Oksak; G. Yar-Mukhamedova; D. Zellele; G. Mussabek; A. Imanbayeva (Eurasian Chemico-Technological Journal)
The complexation behavior in systems containing Ni2+, MoO42−, P2O74−, Cit3− - ions have been thoroughly investigated. The study determined the composition and instability constants of both mono- and biligand complex compounds at a constant ionic strength of the solution (Ic=1). By analyzing the concentration ratios of the complexing agent and ligands, the composition of mono- and polyligand complexes was elucidated. The complexation study utilized the potentiometric method, which is based on the functional dependence of the potential of the indicator electrode on the concentration of the complexing agent ions. The results enabled the calculation of the ionic composition of aqueous solutions of nickel complexes with citrate and diphosphate ions, depending on their concentrations. A proposed scheme for the formation of heteronuclear nickel-molybdenum complexes takes into account the sequence of component introduction into the electrolyte to form complexes of a specific composition. These findings were applied to develop electrolyte compositions for coating with alloys based on iron subgroup metals with molybdenum. These alloys exhibit several valuable properties, including corrosion resistance, electrocatalytic activity in hydrogen production, and enhanced operational characteristics.